Litter Decomposition and Nutrient Dynamics in Tropical Rainforests of Ebom, Southwestern Cameroon: Effects of LoggingDisturbed - Ibrahima, Adamou; Claude Ntonga, Jean; D. Mvondo ZE, Antoine (Global Journal Of Botanical Science, 2016)
The impact of logging on litter decomposition and nutrient release was poorly understood in tropical rainforests. Litter decomposition in situ and nutrient dynamics of selected four tree species, Bubinga (Guibourtia tessmannii (Harms) J. Leonard), Ngon (klainedoxa gobonensis Pierre ex Engl.), Asseng (Musanga cecropioides (Dunal) A. Rich) and Akui (Xylopia aethiopiaca R. Brown ex Tedlie) were compared in undisturbed and logging sites of Ebom tropical rainforest, Southwest Cameroon. After 14 weeks of field experiment, dry mass remaining varied from 43.82% in G. tessmannii to 79.82% in M. cecropioïdes of initial dry mass in undisturbed site, and from 13.36% in G. tessmannii to 81.84% in M. cecropioïdes in the logging site. Decomposition rate constants (k % per week) ranged from 0.02 in M. cecropioides to 0.14 % per. week in G. tessmannii in undisturbed forest and from 0.04 % per week in X. aethiopiaca to 1.7 % per week in G. tessmannii in logging forest. In undisturbed forest, litter of G. tessmannii was rich in initial Nitrogen (N), Magnesium (Mg), Potassium (K) and Phosphorous (P) contents, and poor in initial Calcium (Ca) content. Conversely, litter of M. cecropioides was rich in initial N and Ca contents, and poor in Mg, K and P while that of K. gabonensis was poor in initial N content. Apart from Sodium (Na), all the other nutrients were released from decomposing litter 14 weeks after incubation in undisturbed site with mean released rate between 84.82% for K and 5.41% for P. In both sites, litter decomposition and nutrient dynamics of G. tessmannii were fastest while that of M. cecropioides was lowest and those of the other species intermediate. Initial nutrient content of all species was generally higher in logging site than in undisturbed one, except Ca content in litter of M. cecropioides. Litter decomposition and nutrient releases were similar in logging and undisturbed sites, excepted for G. tessmanni where litter decomposition and nutrient release were higher in logging than undisturbed site. The high turnover of litter and nutrients in logging site suggest that logging activities have little impact on litter decomposition and nutrient dynamics.